2013
DOI: 10.1037/a0030855
|View full text |Cite
|
Sign up to set email alerts
|

The apolipoprotein E genotype predicts longitudinal transitions to mild cognitive impairment but not to Alzheimer's dementia: Findings from a nationally representative study.

Abstract: Objective The ε4 allele of the apolipoprotein E (APOE) genotype is the most widely accepted genetic risk factor for Alzheimer’s dementia (AD), but findings on whether it is a risk factor for the AD prodrome, mild cognitive impairment (MCI), have been inconsistent. In a prospective longitudinal design, we investigated (a) whether transitions to MCI and other forms of neurocognitive impairment without dementia (CIND) are more frequent among normal ε4 carriers than among noncarriers and (b) whether subsequent tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
2
34
1
Order By: Relevance
“…In our study, excluding patients with incident dementia, which limits possible confounding due to incident dementia, did not have a major impact on the results. This indicates that the effects of APOE e4 are not necessarily prodromal to dementia disease and that they might also affect cognitive performance in non-demented people, an interpretation in line with the findings of Brainerd et al [4], who found that APOE e4 increases the rate of transition from normal functioning to cognitive impairment without dementia, but not from cognitive impairment to AD.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In our study, excluding patients with incident dementia, which limits possible confounding due to incident dementia, did not have a major impact on the results. This indicates that the effects of APOE e4 are not necessarily prodromal to dementia disease and that they might also affect cognitive performance in non-demented people, an interpretation in line with the findings of Brainerd et al [4], who found that APOE e4 increases the rate of transition from normal functioning to cognitive impairment without dementia, but not from cognitive impairment to AD.…”
Section: Discussionsupporting
confidence: 78%
“…Also, our sensitivity analyses with amnestic memory and executive function show that associations of APOE e4 in the general population with and without CVD are strongly driven by the memory component of the COGTEL total scores, which supports previous results suggesting that in the general population APOE e4 is only a risk factor for amnestic memory but not for other forms of cognitive impairment [4]. …”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations